ANALISIS THERMAL STRUKTUR SATELIT BENTUK SILINDER - Slamet, Widodo (Indonesian Journal of Aerospace, 2010)
The satellite temperature during its orbit has an extreme value. For this reason, we have to predict the temperature of the satellite structure. A satellite designer needs to analyze the structure temperature based on the heat transfers analysis. Two factorsare needed a view factor and a radiation coupling factor. The thermal distribution on a satellite with cylinder structure under extreme illumination of solar radiation will be analyzed upon its three walls: top, mantle, and bottom of the cylinder.